Predatory insects as biological control agents against walnut aphids in Kashmir, India - Gull, Shaziya (Acta agriculturae Slovenica, 2024)
Management of pests by biological control agents is a natural and environmental friendly method. It is an important part of integrated pest management programs where biological predators play a significant role in controlling various pests. During the present study, different insect pests were observed infesting walnut trees and fruits causing significant damage to the walnut orchards. Among these pests, sap suckers were found to cause notable damage out of which aphids were most dominating pests. High population of walnut aphids causes leaf drop, reduced tree vigour, nut quality and size. In addition to this, some insect predators were also observed on these walnut aphids. Six species of predaceous coccinellid beetles were found on walnut leaves in interaction with walnut aphids and they were identified belonging to sub family Coccinellinae. Among which Calvia punctata (Mulsant, 1853) and Harmonia dimidiata (Fabricius, 1781) were the most encountered species. Besides, one species from syrphidae family Metasyrphus latifasciatus (Macquart, 1859) was also observed. Moreover, extreme feeding potential was noted among these predators.
Keywords: biotično varstvo rastlin; Calvia punctata; coccinellids; Harmonia dimidiata; listne uši; Metasyrphus latifasciatus; oreh; pest management; predatory potential; sap sucker; walnut aphids